Her hidden genius : a novel - Benedict, Marie (Sourcebooks Landmark, 2022)
"Rosalind Franklin knows if she just takes one more X-ray picture-one more after thousands-she can unlock the building blocks of life. Never again will she have to listen to her colleagues complain about her, especially Maurice Wilkins who'd rather conspire about genetics with James Watson and Francis Crick than work alongside her. Then it finally happens-the double helix structure of DNA reveals itself to her with perfect clarity. But what happens next, Rosalind could have never predicted. Marie Benedict's next powerful novel shines a light on a woman who died to discover our very DNA, a woman whose contributions were suppressed by the men around her but whose relentless drive advanced our understanding of humankind"--